The Diversity of Body and Translation: Just a Matter of Perspective - Drößiger, Hans-Harry (Respectus Philologicus, 2019)
The following review concerns the volume Corps et traduction, corps en traduction [Body and Translation, Body in Translation] edited by Solange Hibbs, Adriana Şerban and Nathalie Vincent-Arnaud, published in 2018 by Lambert-Lucas Publishing House in Limoges, France.